Respuesta :
(a) first two overtones for each string:
The first string has a fundamental frequency of 196 Hz. The n-th overtone corresponds to the (n+1)-th harmonic, which can be found by using
[tex]f_n = n f_1[/tex]
where f1 is the fundamental frequency.
So, the first overtone (2nd harmonic) of the string is
[tex]f_2 = 2 f_1 = 2 \cdot 196 Hz = 392 Hz[/tex]
while the second overtone (3rd harmonic) is
[tex]f_3 = 3 f_1 = 3 \cdot 196 Hz = 588 Hz[/tex]
Similarly, for the second string with fundamental frequency [tex]f_1 = 523 Hz[/tex], the first overtone is
[tex]f_2 = 2 f_1 = 2 \cdot 523 Hz = 1046 Hz[/tex]
and the second overtone is
[tex]f_3 = 3 f_1 = 3 \cdot 523 Hz = 1569 Hz[/tex]
(b) The fundamental frequency of a string is given by
[tex]f= \frac{1}{2L} \sqrt{ \frac{T}{\mu} } [/tex]
where L is the string length, T the tension, and [tex]\mu = m/L[/tex] is the mass per unit of length. This part of the problem says that the tension T and the length L of the string are the same, while the masses are different (let's calle them [tex]m_{196}[/tex], the mass of the string of frequency 196 Hz, and [tex]m_{523}[/tex], the mass of the string of frequency 523 Hz.
The ratio between the fundamental frequencies of the two strings is therefore:
[tex] \frac{523 Hz}{196 Hz} = \frac{ \frac{1}{2L} \sqrt{ \frac{T}{m_{523}/L} } }{\frac{1}{2L} \sqrt{ \frac{T}{m_{196}/L} }} [/tex]
and since L and T simplify in the equation, we can find the ratio between the two masses:
[tex] \frac{m_{196}}{m_{523}}=( \frac{523 Hz}{196 Hz} )^2 = 7.1 [/tex]
(c) Now the tension T and the mass per unit of length [tex]\mu[/tex] is the same for the strings, while the lengths are different (let's call them [tex]L_{196}[/tex] and [tex]L_{523}[/tex]). Let's write again the ratio between the two fundamental frequencies
[tex] \frac{523 Hz}{196 Hz}= \frac{ \frac{1}{2L_{523}} \sqrt{ \frac{T}{\mu} } }{\frac{1}{2L_{196}} \sqrt{ \frac{T}{\mu} }}[/tex]
And since T and [tex]\mu[/tex] simplify, we get the ratio between the two lengths:
[tex] \frac{L_{196}}{L_{523}}= \frac{523 Hz}{196 Hz}=2.67 [/tex]
(d) Now the masses m and the lenghts L are the same, while the tensions are different (let's call them [tex]T_{196}[/tex] and [tex]T_{523}[/tex]. Let's write again the ratio of the frequencies:
[tex]\frac{523 Hz}{196 Hz}= \frac{ \frac{1}{2L} \sqrt{ \frac{T_{523}}{m/L} } }{\frac{1}{2L} \sqrt{ \frac{T_{196}}{m/L} }}[/tex]
Now m and L simplify, and we get the ratio between the two tensions:
[tex] \frac{T_{196}}{T_{523}}=( \frac{196 Hz}{523 Hz} )^2=0.14 [/tex]
The first string has a fundamental frequency of 196 Hz. The n-th overtone corresponds to the (n+1)-th harmonic, which can be found by using
[tex]f_n = n f_1[/tex]
where f1 is the fundamental frequency.
So, the first overtone (2nd harmonic) of the string is
[tex]f_2 = 2 f_1 = 2 \cdot 196 Hz = 392 Hz[/tex]
while the second overtone (3rd harmonic) is
[tex]f_3 = 3 f_1 = 3 \cdot 196 Hz = 588 Hz[/tex]
Similarly, for the second string with fundamental frequency [tex]f_1 = 523 Hz[/tex], the first overtone is
[tex]f_2 = 2 f_1 = 2 \cdot 523 Hz = 1046 Hz[/tex]
and the second overtone is
[tex]f_3 = 3 f_1 = 3 \cdot 523 Hz = 1569 Hz[/tex]
(b) The fundamental frequency of a string is given by
[tex]f= \frac{1}{2L} \sqrt{ \frac{T}{\mu} } [/tex]
where L is the string length, T the tension, and [tex]\mu = m/L[/tex] is the mass per unit of length. This part of the problem says that the tension T and the length L of the string are the same, while the masses are different (let's calle them [tex]m_{196}[/tex], the mass of the string of frequency 196 Hz, and [tex]m_{523}[/tex], the mass of the string of frequency 523 Hz.
The ratio between the fundamental frequencies of the two strings is therefore:
[tex] \frac{523 Hz}{196 Hz} = \frac{ \frac{1}{2L} \sqrt{ \frac{T}{m_{523}/L} } }{\frac{1}{2L} \sqrt{ \frac{T}{m_{196}/L} }} [/tex]
and since L and T simplify in the equation, we can find the ratio between the two masses:
[tex] \frac{m_{196}}{m_{523}}=( \frac{523 Hz}{196 Hz} )^2 = 7.1 [/tex]
(c) Now the tension T and the mass per unit of length [tex]\mu[/tex] is the same for the strings, while the lengths are different (let's call them [tex]L_{196}[/tex] and [tex]L_{523}[/tex]). Let's write again the ratio between the two fundamental frequencies
[tex] \frac{523 Hz}{196 Hz}= \frac{ \frac{1}{2L_{523}} \sqrt{ \frac{T}{\mu} } }{\frac{1}{2L_{196}} \sqrt{ \frac{T}{\mu} }}[/tex]
And since T and [tex]\mu[/tex] simplify, we get the ratio between the two lengths:
[tex] \frac{L_{196}}{L_{523}}= \frac{523 Hz}{196 Hz}=2.67 [/tex]
(d) Now the masses m and the lenghts L are the same, while the tensions are different (let's call them [tex]T_{196}[/tex] and [tex]T_{523}[/tex]. Let's write again the ratio of the frequencies:
[tex]\frac{523 Hz}{196 Hz}= \frac{ \frac{1}{2L} \sqrt{ \frac{T_{523}}{m/L} } }{\frac{1}{2L} \sqrt{ \frac{T_{196}}{m/L} }}[/tex]
Now m and L simplify, and we get the ratio between the two tensions:
[tex] \frac{T_{196}}{T_{523}}=( \frac{196 Hz}{523 Hz} )^2=0.14 [/tex]